Analisis Kualitas Hubungan Pemasok terhadap Kepuasan dan Loyalitas Pengelolaan di Toko Madura - Marsono Marsono; Dinda Puspitasari; Sri Devi Pujiati; Intan Ayu Anggraheni; Sri Intan; Iva Novia Magdalena (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The rapid development of the business world has driven increased complexity in competition, particularly in the retail sector which has experienced significant growth in various regions, including Tuban. In this context, the partnership between suppliers and department stores (toserba) becomes a strategic aspect that plays a crucial role in maintaining business continuity, operational efficiency, and customer satisfaction. This study aims to analyze the patterns of relationships between suppliers and department stores in Tuban, as well as to identify factors that support the success of such partnerships and their impact on operational performance and customer satisfaction. Using a qualitative descriptive approach based on library research, data were collected from various secondary sources such as scientific journals, books, and relevant publications. The results indicate that effective partnership relationships are characterized by open communication, high trust and commitment, close collaboration, and adaptation to digital transformation. Furthermore, a solid partnership between suppliers and department stores contributes to improving supply chain efficiency, reducing logistics costs, optimizing inventory management, and enhancing customer satisfaction through product availability and responsive service. This study provides valuable contributions to formulating sustainable collaborative strategies for local retail businesses to face increasingly competitive markets.